The fragmented politics of sugarcane contract farming in Uganda. (27th October 2021) - Martiniello, Giuliano; Owor, Arthur; Bahati, Ibrahim; Branch, Adam
Abstract: In the last decade, contract farming has regained momentum among policymakers and global development agencies as a tool to promote inclusive rural development and responsible investments. Integrating smallholders within global, regional and national agricultural value chains, we are told, represents the sine qua non for alleviating rural poverty. In Uganda, under the label of out‐grower schemes, contract farming is currently undergoing massive expansion, driven especially by the boom in sugarcane cultivation. Drawing from three case studies of sugarcane contract farming in Uganda, the paper re‐politicizes the debate around contract farming by looking at the power relations within which these schemes are embedded. We argue, what is seen in Uganda's expansion is a political dynamic derived both from the major dislocations and dispossessions required to establish the plantation estate and its work force, as well as from the effort to bring many smallholders using unimproved methods on land with sometimes unclear tenure arrangements into contracted arrangements for supplying sugarcane. The result has been highly contentious politics around sugar's expansion, where struggles over land dispossession merge with those around exploitative wage labour, around the loss and transformation of livelihoods, and around debt, power inequalities and environmental harm, a matrix in which state violence and co‐optation are ever‐present.